The SAS Education Value-Added Assessment System (SAS® EVAAS®) in the Houston Independent School District (HISD): Intended and Unintended Consequences - Amrein-Beardsley, Audrey; Collins, Clarin (Education Policy Analysis Archives, 2012)
The SAS Educational Value-Added Assessment System (SAS® EVAAS®) is the most widely used value-added system in the country. It is also self-proclaimed as “the most robust and reliable” system available, with its greatest benefit to help educators improve their teaching practices. This study critically examined the effects of SAS® EVAAS® as experienced by teachers, in one of the largest, high-needs urban school districts in the nation – the Houston Independent School District (HISD). Using a multiple methods approach, this study critically analyzed retrospective quantitative and qualitative data to better comprehend and understand the evidence collected from four teachers whose contracts were not renewed in the summer of 2011, in part given their low SAS® EVAAS® scores. This study also suggests some intended and unintended effects that seem to be occurring as a result of SAS® EVAAS® implementation in HISD. In addition to issues with reliability, bias, teacher attribution, and validity, high-stakes use of SAS® EVAAS® in this district seems to be exacerbating unintended effects.